Trama afetiva da política: uma leitura da filosofia de Espinosa - Braga, Luiz Carlos Montans (2015)
The research started from the relationship among affects, politics and right in Spinoza s philosophy. Indeed, the Ethics Part III is the place where all affects are taken as specific topic. However, the affect subject also appears, in a more or less explicit way, in the exclusively political texts of the author, namely the Theological-Political Treatise and the Political Treatise, in addition to being quickly presented in argumentative moments of the Ethics Part IV, in which the issue of civitas is posed. Another aspect is the presence of the concept of power in the very definition of the concept of affect, in the Ethics Part III, thus closing the circle where the three concepts are presented, because Spinoza identifies right to power (jus sive potentia). The initial hypothesis referred to the existence of ties and intersections between such concepts, which was later confirmed by the detailed reading of Spinoza s texts, as well as of some of his commentators that have worked on the topics presented in the initial issue. The hard core of the dissertation tries to approach this conceptual relationship, explaining it by analyzing the author s texts, namely Ethics, the Theological-Political Treatise and the Political Treatise. In this argumentative proposition, the main thesis I try to defend is that Spinoza creates a political philosophy founded in the theory of affects. From this assumption, a second formulation comes up (but not a second thesis) over the pertinence of Spinoza s concepts for the contemporary emancipatory right. So, the path followed throughout the research has had two approaches, one far more finished and derived from the initial project, which makes an effort to solve the issue hereby posed, and another one more characterized by notes, bringing Spinoza s concept to the analysis of contemporary legal issues. This second moment of the dissertation looks into the pertinence of Spinoza s natural right concept for the contemporary right, besides analyzing the importance of the author s concepts to lend potency to one of the aspects of critical legal studies